PENGEMBANGAN FORMULASI EMULGEL FRAKSI n-HEKSAN DAUN MIANA (Coleus scutellarioides) SEBAGAI ANTIBAKTERI TERHADAP Propionibacterium acnes PENYEBAB JERAWAT (Acne vulgaris) - Auliah, Nielma; Bachri, Nurjannah; SR, Muhammad Asri; Nurfatma, Nurfatma (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Acne (Acne vulgaris) is a condition where the skin experiences inflammation in the polysebaceous unit which is triggered by Propionibacterium acnes. Miana leaves (Coleus scutellarioides) contain alkaloid and terpenoid compounds which can act as antibacterials. This research aims to determine whether the n-hexane fraction of Miana leaves (C. scutellarioides) can be formulated in the form of a physically and chemically stable emulgel preparation, to determine whether the n-hexane fraction of Miana leaves (C. scutellarioides) has activity against P. acnes. as a cause of acne (A. vulgaris) and to determine the formula with an effective concentration in inhibiting the growth of P. acnes. This research is a form of laboratory experimentation. The n-Hexane fraction of miana leaves was obtained by fractionation. Antibacterial activity testing was carried out using the well method. The results obtained were physically and chemically stable emulgel formulas, namely F0 and F1. The inhibition zone of F1 is 16.46 mm (strong), F2 is 14.40 mm (strong), F3 is 16.78 mm (strong) and F0 has no antibacterial activity. The formula with a concentration of 12.5% was the most effective in inhibiting the growth of P. acnes, namely 16.78 mm. From the results of this research, it was found that the n-Hexane fraction of Miana leaves (C. scutellarioides) has strong antibacterial activity against P. acnes and can be formulated in the form of an emulgel dosage form.